2022
DOI: 10.3390/app12189117
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Programmes in the Treatment of Addictions: A Systematic Review

Abstract: The scientific literature was reviewed with the aim of determining the current state of the research on relationships between physical activity programmes and addiction treatment. Methods: The search was carried out in the WOS, Scopus and PubMed databases, restricting the publication language to English and Spanish, and it was limited to studies conducted in the last 5 years, i.e., between 1 January 2016 and 31 November 2021, selecting only open-access articles with physical activity programmes for the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Several reviews and meta-analyses have documented the importance of physical activity and exercise programs in the treatment of addictions in various age groups and settings [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In general, intervention programs have shown positive effects, encompassing a reduction in anxiety and depressive symptoms, enhanced working memory, increased self-confidence, improved self-esteem, positive changes in body image, mood enhancement, elevated well-being and quality of life, alterations in behavior, and positive lifestyle changes.…”
Section: The Role Of Exercise In Sud Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews and meta-analyses have documented the importance of physical activity and exercise programs in the treatment of addictions in various age groups and settings [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In general, intervention programs have shown positive effects, encompassing a reduction in anxiety and depressive symptoms, enhanced working memory, increased self-confidence, improved self-esteem, positive changes in body image, mood enhancement, elevated well-being and quality of life, alterations in behavior, and positive lifestyle changes.…”
Section: The Role Of Exercise In Sud Treatmentmentioning
confidence: 99%
“…A relevant review showed that physical activity has been incorporated into treatments in combination with other pharmacological or behavioral treatments. Healthy nutrition to achieve optimal health and well-being should also enrich these new habits [ 11 ]. Adapting to the participants’ levels is crucial.…”
Section: Integrating Exercise Into Sud Recovery: Cognitive–behavioral...mentioning
confidence: 99%
“…These aspects include the impact on mental health, the prevention of chronic illness, and the socio-cultural impacts on involvement. Several studies have demonstrated that there is a beneficial correlation between engaging in physical exercise and maintaining adherence to treatment for addiction [16]. When it comes to adults, there is substantial evidence that physical exercise helps prevent weight gain, particularly when the intensity of the activity ranges from moderate to strenuous [17].…”
Section: Current State Of the Literaturementioning
confidence: 99%
“…Los programas de actividad física mejoran la calidad de vida, la calidad del sueño y el estado de ánimo, y reducen el riesgo de exclusión social. Asimismo, reduce directamente el sedentarismo, responsable de más de cuarenta enfermedades y trastornos crónicos 4 . Es por ello, que es necesario el fomento de los talleres de actividad física saludable en los pacientes seropositivos porque esto permitirá mejorar la condición física y evitar la aparición de enfermedades oportunistas y, además, mejorar su salud mental.…”
Section: Importance Of Physical Therapy and Rehabilitation In The Car...unclassified